2019
DOI: 10.1002/hep.30472
|View full text |Cite
|
Sign up to set email alerts
|

Ductular Reaction Cells Display an Inflammatory Profile and Recruit Neutrophils in Alcoholic Hepatitis

Abstract: Chronic liver diseases are characterized by the expansion of ductular reaction (DR) cells and the expression of liver progenitor cell (LPC) markers. In alcoholic hepatitis (AH), the degree of DR expansion correlates with disease progression and short‐term survival. However, little is known about the biological properties of DR cells, their impact on the pathogenesis of human liver disease, and their contribution to tissue repair. In this study, we have evaluated the transcriptomic profile of DR cells by laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 47 publications
1
47
1
Order By: Relevance
“…BD organoid cells were also expressed various Wnt ligands with described canonical and non-canonical activity, with Wnt7b, Wnt7a and Wnt4 the most abundantly expressed (Figure 4, J) (Eubelen et al, 2018; Vallon et al, 2018; Yu et al, 2008) (Alok et al, 2017; Cho et al, 2017; Ferrari et al, 2018; Le Grand et al, 2009; Posokhova et al, 2015). To assess whether the panel of Wnts expressed by BD organoids might be relevant in a clinical setting, we examined the expression of Wnt ligands in the ductal reactions of human cirrhotic patients using the public data from laser capture microdissection (LCM) experiments (Aguilar Bravo et al, 2019). Wnt7b was the most abundantly expressed Wnt ligand in ductal reactions of cirrhotic human samples dissected based on CK7+ expression, suggesting that the biliary epithelium might be an important contributing source to the ductal reactions Wnt microenvironment of these patients (Figure 4, K).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BD organoid cells were also expressed various Wnt ligands with described canonical and non-canonical activity, with Wnt7b, Wnt7a and Wnt4 the most abundantly expressed (Figure 4, J) (Eubelen et al, 2018; Vallon et al, 2018; Yu et al, 2008) (Alok et al, 2017; Cho et al, 2017; Ferrari et al, 2018; Le Grand et al, 2009; Posokhova et al, 2015). To assess whether the panel of Wnts expressed by BD organoids might be relevant in a clinical setting, we examined the expression of Wnt ligands in the ductal reactions of human cirrhotic patients using the public data from laser capture microdissection (LCM) experiments (Aguilar Bravo et al, 2019). Wnt7b was the most abundantly expressed Wnt ligand in ductal reactions of cirrhotic human samples dissected based on CK7+ expression, suggesting that the biliary epithelium might be an important contributing source to the ductal reactions Wnt microenvironment of these patients (Figure 4, K).…”
Section: Resultsmentioning
confidence: 99%
“…Organoids primarily expressed Wnt4, Wnt7b and Wnt7a and Rspo1 HPC-induced signature was dependent on these endogenously produced Wnt ligands. Of the organoid expressed ligands, Wnt7b was strongly expressed in DR of human cirrhotic patients (Aguilar Bravo et al, 2019). A range of other studies also demonstrated expression of Wnt7a and Wnt7b ligands in BECs following liver injury (Okabe et al, 2016; Pepe-Mooney et al, 2019;Boulter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Related studies have shown that DRCs are a cell group different from liver progenitor cells (HPCs) and have their unique repair function. 36 An essential prerequisite for biliary repair is that DRCs can reconstruct the biliary structure. 37 In this study, In DR studies, EpCAM and SOX9 are often identified as stem cell markers.…”
Section: Discussionmentioning
confidence: 99%
“…14 Similarly, a role for neutrophils in the pathogenesis of AH has always been presumed, and in fact their presence in the hepatic lobule is part of the criteria for histological diagnosis. 12 However, to our knowledge, it has not previously been considered that neutrophils interact with cholangiocytes in this disease (except for with reactive bile ducts), 52 nor that their interaction must include direct contact. By providing evidence that neutrophils bind to cholangiocytes via ITGB1 in AH and that the degree of interaction reflects the degree of jaundice (figures 1 and 6), the current work provides unexpected new cell and molecular targets for therapy.…”
Section: Figurementioning
confidence: 93%